Prevention and treatment of rheumatoid arthritis through traditional Chinese medicine: role of the gut microbiota - Liang, Yujiao; Liu, Mengyao; Cheng, Yingxue; Wang, Xinchang; Wang, Weijie (Frontiers in Immunology, 2023)
Recently, despite the increasing availability of treatments for Rheumatoid arthritis (RA), the incidence of RA and associated disabilityadjusted life years have been on the rise globally in the late decades. At present, accumulating evidence has been advanced that RA is related to the gut microbiota, therefore, the therapeutic approaches for RA by regulating the gut microbiota are anticipated to become a new means of treatment. Traditional Chinese medicine (TCM) can regulate immunity, reduce inflammation and improve quality of life in various ways. Moreover, it can treat diseases by affecting the gut microbiota, which is a good way to treat RA. In this review, we mainly explore the relationship between TCM and gut microbiota regarding the perspective of treating RA. Moreover, we comprehensively summarize the roles of gut microbiota in the onset, development, progression, and prognosis of RA. Additionally, we elucidate the mechanism of TCM prevention and treatment of RA by the role of microbiota. Finally, we provide an evidence-based rationale for further investigation of microbiota-targeted intervention by TCM.